Implementasi Akuntansi Pesantren Berbasis ISAK 35 di Madura - Aulia, Fena Ulfa; Kulsum, Ummu; Laila, Nur; Wulandari, Sitti (Universitas Islam Negeri Sumatera Utara, 2024)
This research aims to identify and explore the extent to which Islamic boarding school accounting implementation in Madura is in accordance with ISAK 35 standards. Madura is known as a religious island with a majority Muslim population that still upholds religious values, besides being known as the religious island of Madura, it is also known as the island of santri, Due to the large number of Islamic boarding schools being established, currently the number of Islamic boarding schools in Madura is 1,386. In general, Islamic boarding schools in Madura are established in the form of foundations which are a form of non-profit organization founded by the community or a group of people and whose main aim is to provide social services without focusing on achieving profits. This research uses a descriptive qualitative approach, with primary data obtained through interviews and triangulation methods. This study was conducted at three Islamic boarding schools in three districts in Madura. The research results show that the three Islamic boarding schools have not implemented Islamic boarding school accounting in accordance with ISAK 35. The financial reports prepared are still simple and do not follow established accounting standards. In conclusion, the implementation of Islamic boarding school accounting in Madura is implemented differently with different formats in each Islamic boarding school because it does not yet refer to ISAK 35 due to limited human resources and unknowledge of Islamic boarding school administrators regarding accounting science